Incidence of gastric cancer, its subtypes, and correlation with Helicobacter Pylori - KC, Shiva Raj; Amatya, GL; Lakhey, A; Basnet, S; Aryal, G (Journal of Pathology of Nepal, 2013)
Background: Gastric cancer is the fourth most commonly diagnosed cancer and the second most common cause of cancer related death worldwide. It is the common cause of cancer related death in Nepal. Helicobacter Pylori has been classified as a definite carcinogen along with other factors. The aim of this study was to fi nd the incidence of gastric cancer among the patients undergoing upper gastroscopy, its various subtypes and association with Helicobacter Pylori. Materials and Methods: This is a retrospective and prospective study carried out at GRP Polyclinic and Kist Medical College Teaching Hospital. All the patients undergoing upper gastrointestinal endoscopy were included in this study. Data of all the gastric endoscopic biopsies done from June 2011 to January 2013 were collected and analyzed. All the biopsy specimens were processed routinely in histopathology laboratory. Specimens showing carcinoma were enrolled in this study and all the relevant demographic data were collected. Results: Out of 3395 biopsy cases; 49 cases (1.44%) were diagnosed as adenocarcinoma stomach. The overall mean age for carcinoma was 47.6 years with a mild male preponderance. Thirty cases (61.2%) were of intestinal type, (n=11; 22.4%) were of diffuse type and (n=8; 16.3%) were mixed type of adenocarcinoma. According to WHO classifi cation the most common subtype was tubular adenocarcinoma (n=35; 71.5%) followed by signet ring type (11 cases; 22.4%). Out of 49 cases of adenocarcinoma stomach 39 cases (79.5%) were Helicobacter Pylori positive. Conclusion: This study shows that gastric carcinoma is a male predominant neoplasm usually of old age but can occur at younger ages. It predominantly occurs in Helicobacter Pylori infected patients and H. Pylori eradication will help to decrease the incidence rate and mortality of stomach cancer. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 403-407 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7869